2017
DOI: 10.1002/ccr3.1100
|View full text |Cite
|
Sign up to set email alerts
|

Physical rehabilitation modulates microRNAs involved in multiple sclerosis: a case report

Abstract: Key Clinical MessageThis study shows that neuromuscular taping improves gait, balance, pain and ability to walk and conduct daily activities in a multiple sclerosis patient. It is the first study to identify a panel of miRNAs modulated throughout rehabilitation using neuromuscular taping in a multiple sclerosis patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Cases related to NMT in this article include foot problems of athletes, multiple sclerosis, cerebral palsy hemiplegia and post-stroke upper limbs, and Joint Hypermobility Syndrome of the lower extremities. Case reports on multiple sclerosis indicated that NMT was able to affect the modulation of micro Ribonucleic Acids (miRNAs) during the rehabilitation phase (Vallelunga et al, 2017). The risk of impaired mobility also increases Type 2 Diabetes Mellitus (DM) patients in the elderly (6%/year), peripheral neuropathy (40%), history of stroke (123%), insulin therapy (117%), and arthritis (82%), which will affect Activities of Daily Living (ADL) (Bianchi et al, 2013;Bruce et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Cases related to NMT in this article include foot problems of athletes, multiple sclerosis, cerebral palsy hemiplegia and post-stroke upper limbs, and Joint Hypermobility Syndrome of the lower extremities. Case reports on multiple sclerosis indicated that NMT was able to affect the modulation of micro Ribonucleic Acids (miRNAs) during the rehabilitation phase (Vallelunga et al, 2017). The risk of impaired mobility also increases Type 2 Diabetes Mellitus (DM) patients in the elderly (6%/year), peripheral neuropathy (40%), history of stroke (123%), insulin therapy (117%), and arthritis (82%), which will affect Activities of Daily Living (ADL) (Bianchi et al, 2013;Bruce et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, kinesiology tape is a valid method to decrease spasticity and related signs in a short time and make better stability and gait in chronic incomplete spinal cord injuries participants (9). Additionally, neuromuscular taping improved gait, balance, pain, and ability to walk and conduct daily activities in multiple sclerosis patients (21,22). The Ankle and leg balance -Significant statistical differences were observed before taping in all sensory organization test parameters between stroke and control groups (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…As result, local nociceptive and inflammatory mediators may be reabsorbed [ 112 ]. Other types of compressive treatments, such as neuromuscular taping, which also increase lymphatic and vascular flow, strengthening weakened muscles, led to the identification of a panel of miRNAs that changed with treatment in a multiple sclerosis (MS) patient [ 113 ]. Interestingly enough, some of these miRNAs have been shown to appear deregulated, both in FM [ 16 , 93 , 114 ] and in CFS/ME patients [ 88 ] suggesting that compressive treatments might provide therapeutic benefits for them as well.…”
Section: The Rationale For Using Mt To Treat Fm and Cfs/me Dysfuncmentioning
confidence: 99%